2019
DOI: 10.18203/2320-6012.ijrms20190940
|View full text |Cite
|
Sign up to set email alerts
|

Can serum ferritin levels predict the severity of dengue early?: an observational study

Abstract: Background: Dengue infection is a major public health threat; early recognition is crucial to improve the survival in severe dengue. Although there are various biomarkers to predict the severity of dengue, they are not routinely used in clinical practice for prognostication. We analyzed whether serum ferritin can be used to predict the severity at an earlier stage.Methods: A hospital based prospective observational study was done involving 119 dengue cases diagnosed by positive NS1 antigen or dengue specific s… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

4
11
1

Year Published

2019
2019
2023
2023

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 11 publications
(16 citation statements)
references
References 9 publications
(19 reference statements)
4
11
1
Order By: Relevance
“…There was significant thrombocytopinea in patients having high serum Ferritin level. These findings are in concordance with Jyothi S et al 2018 [13,14] . Hyper-ferritinemia in dengue fever is associated with elevation of SGOT, SGPT and serum creatinine.…”
Section: Discussionsupporting
confidence: 92%
“…There was significant thrombocytopinea in patients having high serum Ferritin level. These findings are in concordance with Jyothi S et al 2018 [13,14] . Hyper-ferritinemia in dengue fever is associated with elevation of SGOT, SGPT and serum creatinine.…”
Section: Discussionsupporting
confidence: 92%
“…12 Coincidental findings were made in a study in Singapore; people over 60 years of age had more extreme dengue occurrence (20.3 percent vs. 14). [12][13][14] Our study show 1,200 ng / ml serum ferritin cut-off level was used to predict the clinical manifestation of DHF. During Days 5, 6, and 7 after the onset of fever, the results for sensitivity were 83, 86, and 92 per cent respectively.…”
Section: Discussionmentioning
confidence: 80%
“…Petchiappan et al 29 noted higher ferritin levels were reported on D4 onward during the febrile phase of illness (within 7 days of onset of illness) in severe dengue patients than nonsevere dengue cases. Our study demonstrated an increase in ferritin levels as the severity grade increases and analyzed serum ferritin levels both during febrile, defervescence, or convalescent phase, which is critical as the disease progression to severe dengue occurs after the febrile phase.…”
Section: Discussionmentioning
confidence: 97%
“…Our study also had a higher number of severe dengue cases than this study. 29 Furthermore, in another study in Aruba, which compared serum ferritin levels of 44 dengue patients with those of other febrile illnesses (OFIs), and found significantly elevated ferritin levels on days 6-8 of illness in dengue patients. The higher ferritin levels in dengue patients were associated with higher viral copy numbers on days 2-3 of illness.…”
Section: Discussionmentioning
confidence: 99%